Ֆրանկոֆոնիայի 17-րդ գագաթնաժողովը Երևանում - Վարդերեսյան, Հռիփսիմե Է. (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
В 2018 году в Армении прошел 17-й Саммит Франкофонии под названием «Жить вместе, уважая солидарность, гуманитарные ценности и разнообразие, как основа мира и благополучия во франкоязычном регионе». Саммит собрал делегации 84 стран во главе с лидерами 38 стран. The 17th Summit of la Francophonie was held in Armenia in 2018 with the title "Living together, respecting solidarity, humanitarian values and diversity as a basis for peace and welfare in the Francophone region". The summit brought together the delegations of 84 countries, led by the leaders of 38 countries.
Keywords: Հայոց պատմություն; Միջազգային կազմակերպություններ; Միջազգային հարաբերություններ; Միջազգային համաժողովներ